2014
DOI: 10.1586/14789450.2014.933673
|View full text |Cite
|
Sign up to set email alerts
|

Advances in endothelial shear stress proteomics

Abstract: The vascular endothelium lining the luminal surface of all blood vessels is constantly exposed to shear stress exerted by the flowing blood. Blood flow with high laminar shear stress confers protection by activation of antiatherogenic, antithrombotic and anti-inflammatory proteins, whereas low or oscillatory shear stress may promote endothelial dysfunction, thereby contributing to cardiovascular disease. Despite the usefulness of proteomic techniques in medical research, however, there are relatively few repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 99 publications
0
10
0
2
Order By: Relevance
“…Atherosclerosis develops at sites of disturbed flow, but less in regions with steady laminar flow [2]. Previous studies have shown that laminar flow confers atheroprotection by activating anti-atherogenic, anti-thrombotic and anti-inflammatory signaling pathways, whereas disturbed flow promotes endothelial dysfunction thereby contributing to the development of atherosclerosis-related cardiovascular diseases [37]. Specifically, the endothelium in the atheroprotective regions, in comparison to that in atheroprone regions, shows increased expression of Kruppel-like factor 2 (KLF2), increased production of NO derived from activated eNOS, decreased leukocyte adhesion and vascular permeability, as well as other atheroprotective phenotypes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Atherosclerosis develops at sites of disturbed flow, but less in regions with steady laminar flow [2]. Previous studies have shown that laminar flow confers atheroprotection by activating anti-atherogenic, anti-thrombotic and anti-inflammatory signaling pathways, whereas disturbed flow promotes endothelial dysfunction thereby contributing to the development of atherosclerosis-related cardiovascular diseases [37]. Specifically, the endothelium in the atheroprotective regions, in comparison to that in atheroprone regions, shows increased expression of Kruppel-like factor 2 (KLF2), increased production of NO derived from activated eNOS, decreased leukocyte adhesion and vascular permeability, as well as other atheroprotective phenotypes [38].…”
Section: Discussionmentioning
confidence: 99%
“…Hemodynamic forces in pulmonary circulation contribute to endothelial cell phenotype mainly through shear stress [5]. Overall physiological shear stress can vary from high (15 dynes/cm 2 ) to low (4 dynes/cm 2 ) in lung arterial tree [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, such approaches failed to reveal important post-transcriptional protein control mechanisms in the endothelium. In the past decade, some studies have conducted proteome analysis of cultured vascular endothelial cells from bovine, rat, mice, and humans under different shear stresses (Wang et al, 2007 ; Freed and Greene, 2010 ; Firasat et al, 2014 ). However, the biological role of the secretome in LSM from underlying endothelial cells exposed to the LSS remains unclear.…”
Section: Introductionmentioning
confidence: 99%